Le revenu universel - Mateo Alaluf; Marie-Pierre Boucher; Jean-Marie Harribey; Sandra Laugier; Raphaël Liogier; Sabine Fortino; Jean-Pierre Durand (La Nouvelle Revue du Travail)
The reflections offered in Controverses are congruent with Corpus “Working more” texts’ scrutiny of workers’ motivations and commitments, hence analysis of societies where income is directly related to the work people do, with a minority of varying size being allocated benefits by the rest of the community. The questions that then arise include how to justify morally and politically the idea that people might have the right to a basic income; what effects this sort of income would have on society as a whole; how the relationship between working and not working might be organised; whether this constitutes the oft-heralded “end of work”; what the economic foundations of a basic income might be; how to conceptualise the relationship to basic income of authorities responsible for paying benefits to unemployed persons meant to rejoin the work force; and what macro-economic effects this would all have. The article features five economics or sociology researchers answering these questions and arguing for or against the feasability of a basic income.